2018
DOI: 10.1186/s12889-018-5618-z
|View full text |Cite
|
Sign up to set email alerts
|

Perceived stress as a risk factor of unemployment: a register-based cohort study

Abstract: BackgroundAlthough unemployment and high levels of perceived stress have been associated in cross-sectional studies, the direction of causation is unknown. We prospectively examined if high levels of perceived everyday life stress increased the risk of subsequent unemployment and further if differences existed between socioeconomic status-groups.MethodsWe included 9335 18–64-year-old employed respondents of a health survey (North Denmark Health Profile 2010) in which Cohen’s Perceived Stress Scale was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 33 publications
5
27
0
3
Order By: Relevance
“…The unemployed had a higher prevalence of stress only because of their male counterparts, which suggests that stress was more related to unemployment among men than women. This is confirmed by the literature, where a cohort study by Maehlisen MH, et al (2018) found that domestic stress almost doubled the risk of unemployment [15].…”
Section: Resultssupporting
confidence: 74%
“…The unemployed had a higher prevalence of stress only because of their male counterparts, which suggests that stress was more related to unemployment among men than women. This is confirmed by the literature, where a cohort study by Maehlisen MH, et al (2018) found that domestic stress almost doubled the risk of unemployment [15].…”
Section: Resultssupporting
confidence: 74%
“…However, an absolute causal relationship could not be established. In a sample of 224 participants, 10.4% had high stress amidst unemployment (Mæhlisen et al 2018 ). The unemployed being significantly stressed may suggest a causal relationship, but causality can not be established until additional investigations are performed.…”
Section: Discussionmentioning
confidence: 99%
“…In this setting, the prevalence rates reported from other countries around the world have revealed substantial variability suggesting that both local social and cultural factors, as well as the underlying common elements promoting the emergence of depression, anxiety, and stress, may lead to marked heterogeneity in the prevalence rates of these psychiatric disturbances. Notwithstanding, higher prevalence of these psychiatric symptoms is universally more likely to occur among unemployed graduates all over the world (26). Previous studies have reported elevated rates of depression, anxiety, and stress among involuntarily unemployed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…UUE-related elements such as economic distress and joblessness, as well as job insecurity, frequently underlie feelings of failure, which in turn may lead to depression, stress, and anxiety (36). Moreover, the family and social pressures associated with job-seeking activities and higher expectations from university graduates also act as potential mediators of depression and stress disorders among university graduates exploring the job markets (2).…”
Section: Introductionmentioning
confidence: 99%